KṚTANGARADUHITA: PERANAN DAN KEDUDUKAN MEREKA DI KERAJAAN MAJAPAHIT - Nastiti, Titi Surti (AMERTA, 2012)
Kṛtanagaraduhita: Role and Their Status in Majapahit Kingdom. According to primarytextual data such as inscriptions and Nāgarakṛtāgama text. There were mentions that Raden Wijaya the founder of Majapahit kingdom had four wives. The four wives were daughters of Kṛtanagara (Kṛtanagaraduhita). Kṛtanagara (Kṛtanagaraduhita) died from Jayakatatyĕng or Jayakatwang attack. In this paper we will discuss pertaining the role of Raden Wijaya wives in Majapahit Kingdom. We will also discuss why did the youngest daughter of Kṛtanagara, Gayatrī or Rajapatnī had a more important role and stature in the Majapahit Kingdom than the eldest daughter Tribhuwaneśwarī.